2020
DOI: 10.3390/app10030989
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Sensing of Touch and Pressure by Using Highly Elastic e-Fabrics

Abstract: In recent years, electronic skins have been widely studied for human monitoring systems. This research field needs multi-sensing points for large deformation, strong recovery, and mass production methods. Toward these aims, the fabrication of e-fabric skins made from a capacitive touch sensing layer and a capacitive pressure sensing layer is presented in the paper. Due to the high elasticity of the dielectric layer of the spacer fabric, this structure exhibits a very fast recovery time (6 ms), low hysteresis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Vu et al 106 (Figure 2b) reported on the fabrication of efabric skin with fast response-recovery time, by combining two sensor layers. The sensors were made by screen printing of commercial ink containing single-walled CNT (SWCNT) and silver particles stretchable ink.…”
Section: Soft Electronics Fabrication Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vu et al 106 (Figure 2b) reported on the fabrication of efabric skin with fast response-recovery time, by combining two sensor layers. The sensors were made by screen printing of commercial ink containing single-walled CNT (SWCNT) and silver particles stretchable ink.…”
Section: Soft Electronics Fabrication Approachesmentioning
confidence: 99%
“…(B) Structure of the capacitive sensor layer, real picture of the capacitive sensor layer, and working principle of the capacitive sensor layer. Reprinted with permission from ref . Copyright 2020 MDPI.…”
Section: Soft Electronics Fabrication Approachesmentioning
confidence: 99%
“…Furthermore, as the demand for facile integration, increasing complexity, and customized electronic devices rises, the need for efficient and precise manufacturing techniques grows. , Thus, additive manufacturing technologies, including inkjet printing, gravure, , screen printing, and direct-ink writing (DIW), , have been used to deposit various conductive and nonconductive functional patterns on rigid and flexible substrates. Screen printing is an additive manufacturing technique with superior material utilization, low process temperatures, the ability to handle large-scale production at low cost, and a printing process fast enough for mass production .…”
Section: Introductionmentioning
confidence: 99%
“…providing linear correlation between an applying force and a change in capacitance and exhibiting less hysteresis behavior during an operation. 8) One of the materials famously used in such sensors is polydimethylsiloxane (PDMS) owing to an excellence in mechanical properties, less toxicity, and biocompatibility as well as being simple to fabricate. [9][10][11] However, capacitive force sensor based on PDMS encounters limitations in low sensitivity and slow response/recovery time.…”
Section: Introductionmentioning
confidence: 99%